2008
DOI: 10.1136/bjo.2007.136168
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cataract surgical services in children: an example from Tanzania

Abstract: Practical application of a measure of service delivery for childhood cataract has been useful in identifying gaps in utilisation of existing services by region as well as by gender. Testing in other settings would be helpful. An apparent inequity in use of services by girls requires attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…This is similar to observations in other sub-Saharan African countries where two-thirds of pediatric cataract operations are done on boys. [2][3][4][5] As observed in Kenya, the disparity observed in our study is likely to be due to gender roles in the community. [4] Male genetic predisposition to congenital and developmental cataract is also unlikely, given that a recent study conducted in Denmark revealed no male genetic predisposition.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…This is similar to observations in other sub-Saharan African countries where two-thirds of pediatric cataract operations are done on boys. [2][3][4][5] As observed in Kenya, the disparity observed in our study is likely to be due to gender roles in the community. [4] Male genetic predisposition to congenital and developmental cataract is also unlikely, given that a recent study conducted in Denmark revealed no male genetic predisposition.…”
Section: Discussionmentioning
confidence: 85%
“…This figure does not compare favorably with an overall CCSR of 9 in Tanzania. [2] Though we do not have estimates for the incidence of traumatic cataracts, these figures alone suggest that this part of Madagascar is underserved with pediatric cataract surgical services. Possible reasons for these low figures are lack of awareness that children can also have cataract and that it should be treated early.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…13 Distance from the hospital is one of the most important factors contributing to delay in the developing world of pediatric cataract surgery. 18 Furthermore, most surgical procedures require a provider to administer general anesthesia to infants and young children. In many rural regions, access to a trained anesthesiologist may be difficult, and most anesthesia is provided by minimally trained technicians.…”
Section: Current Limitationsmentioning
confidence: 99%